A educação em tempos de mudança: os contributos do projeto laboratório dos novos tempos (PLNT) - Oliveira, Gilvando Inácio de (2022)
This article aims to report the possibilities of change in school practices of the Project Laboratory of New Times - (PLNT), linked to the formative actions of the NGO - CEAP (Centre for Studies and Pedagogical Advice), based in Salvador da Bahia. The Laboratory is dedicated to the construction of innovative methodologies, appropriating itself to a pedagogical practice centred on creativity, protagonism, self-didacticism, problem-solving capacity and autonomy in students' learning. We used a qualitative methodology. It was found that the project's formative actions broke the traditional practices and played an active role in the socio-political reality of the students, connecting all pedagogical actions with global events. The pedagogical action of learning with technological mediation, valued the students' socio-educational context and their possibilities of emancipation.